2015
DOI: 10.1007/s10151-015-1267-8
|View full text |Cite
|
Sign up to set email alerts
|

European consensus meeting of ARM-Net members concerning diagnosis and early management of newborns with anorectal malformations

Abstract: The ARM-Net (anorectal malformation network) consortium held a consensus meeting in which the classification of ARM and preoperative workup were evaluated with the aim of improving monitoring of treatment and outcome. The Krickenbeck classification of ARM and preoperative workup suggested by Levitt and Peña, used as a template, were discussed, and a collaborative consensus was achieved. The Krickenbeck classification is appropriate in describing ARM for clinical use. The preoperative workup was slightly modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 9 publications
0
46
0
Order By: Relevance
“…In contrast, a diverting colostomy followed by posterior sagittal anorectoplasty is performed for an intermediate-or high-type imperforate anus. [2][3][4][5] Prone cross-table radiography is currently the most widely used imaging method for classifying an imperforate anus. 4,6,7 Prone cross-table radiography is indicated in cases with no visible fistula, normal buttocks, a normal spine, a normal sacrum, and negative urinalysis results for meconium.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, a diverting colostomy followed by posterior sagittal anorectoplasty is performed for an intermediate-or high-type imperforate anus. [2][3][4][5] Prone cross-table radiography is currently the most widely used imaging method for classifying an imperforate anus. 4,6,7 Prone cross-table radiography is indicated in cases with no visible fistula, normal buttocks, a normal spine, a normal sacrum, and negative urinalysis results for meconium.…”
mentioning
confidence: 99%
“…[2][3][4][5] Prone cross-table radiography is currently the most widely used imaging method for classifying an imperforate anus. 4,6,7 Prone cross-table radiography is indicated in cases with no visible fistula, normal buttocks, a normal spine, a normal sacrum, and negative urinalysis results for meconium. 4 Prone cross-table radiography should be performed 20 to 24 hours after the initial examination to allow time for intraluminal pressure in the rectal pouch to increase.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of ARMs in our series was mainly clinical, including routine imaging (thoracic, abdominal, pelvic and spinal X-rays) and invertography, abdominal ultrasound and contrast studies, along with endoscopic evaluation that aimed to evaluate the topography and extent of the lesion. The recent ARM-Net meeting brought minor changes to the preoperative management of ARMs regarding the 24 hours re-evaluation and cross-table lateral X-ray, compared to Levitt and Peña's flow chart [23,24]. It was suggested that in a newborn male with a perineal fistula, a cross-table lateral X-ray is unnecessary, this procedure being recommended only in cases of normal buttocks, normal spine, normal sacrum, and negative urinalysis on meconium; this protocol was extended to female neonates with visible fistula.…”
Section: Discussionmentioning
confidence: 99%